Trend Research on STEM Learning Trough Bibliometric Mapping Analysis: Contribution to Science Education Undergraduate Program - Fatimah, Siti; Chamdani, Muhammad; Syahidi, Khaerus; Mahmudah, Umi (Mataram University, 2024)
This study aims to analyze the trend of STEM research publications in undergraduate education each year, visualize the trend of STEM research in undergraduate education, and how STEM research contributes to undergraduate science education. This study was conducted in September 2023 using bibliometric analysis. This study uses the following search terms in the title, abstract, and keywords: